Frequency and types of revision made in wiki assisted writing classroom - Yusoff, Zailin Shah; Mat Daud, Nuraihan (IDOSI Publication, 2013)
Some writing classrooms have included the use of computer-mediated communication (CMC) online tools to facilitate and enhance students’ writing process. This case study investigates how one of the tools, namely wiki can be used in writing as a process (versus writing as a product) activity in providing feedback to students’ academic report. Data consisted of the feedback given and revisions made by ESL engineering students via wiki. The students’ first and final drafts were also evaluated for writing improvement. In addition, they were interviewed using semi-structured interview technique. Findings show that they made various surface level revisions after receiving feedback via wiki and these revisions resulted in an improvement in their final draft. The findings of the study suggest that wiki provides a platform for process writing activities without the need for face-to-face interaction. However, a supportive teaching and learning environment is essential to ensure a greater impact of the tool on process writing activities.